Susceptibilidad a deslizamientos en la vía de integración barrial con un tramo de 1.5 Km desde el redondel de Carigán hacia la avenida 8 de diciembre ubicada en la ciudad, cantón y provincia de Loja. - Morocho Pizarro, René Marcelo (2018)
The purpose of this thesis is to identify and characterize the areas prone to landslides in the neighborhood integration path with a 1.5 km stretch from the Carigan ring road to the 8 de December Avenue located in the City, Canton and Province of Loja. In this project, field and office work was carried out to obtain data in the different surveys: Topographic, Geological, Geomorphology, Slopes, Current land use and Isoyetas as a triggering factor; likewise, indirect methods such as vertical electrical probes were used, which helped us to determine the lithology and water content in the strata in the study sector. To obtain the final Map of Susceptibility to landslides, the Multicriteria Evaluation Method (EMC) was used, which constitutes a very efficient methodology for the elaboration of those maps implemented in SIG. The initial normalization and weighting of the maps is through the Matrix. Of Saaty Analytical Hierarchy (AHP), as a result the maps of the variables with their respective weights: Geomorphology (0.29), Geology (0.19), Current land use (0.19), Isohyets (0.19), Slope (0.13). The obtaining of the final map was obtained by means of the sum tool pondered in ArcGis. 10.2 and represented by a "Model Builder". The final result was the susceptibility categorized into 3 classes according to the criteria of Sakar and Kanungo (2004); reflecting that the majority of the study area has a Low category of 42.8 (Ha), Medium 22.55 (Ha) and High 9.2 (Ha), it is last located in much of the Trigal formation and slopes of the roads and steep slopes. The results of this project will allow to zonify the susceptible areas to slide in such a way that it is a base for the application of public policies focused on the prevention of risks in the road and its surroundings, besides being key elements within the planning and development projects and Land Management.